The rate of decay of fresh fission products from a nuclear reactor - Dolan, David J., author; Johnson, Thomas, advisor; Brandl, Alexander, committee member; Desir, Rosemond, committee member (Colorado State University. Libraries, 2013)
Determining the rate of decay of fresh fission products from a nuclear reactor is complex because of the number of isotopes involved, different types of decay, half-lives of the isotopes, and some isotopes decay into other radioactive isotopes. Traditionally, a simplified rule of t-1.2 or 7s and 10s is used to determine the dose rate from nuclear weapons and can be to estimate the dose rate from fresh fission products of a nuclear reactor. An experiment was designed to determine the dose rate with respect to time from fresh fission products of a nuclear reactor. The experiment exposed 0.5 grams of U3O8 to a fast and thermal neutron flux from a TRIGA Research Reactor (Lakewood, CO) for ten minutes. The dose rate from the fission products was measured by four Mirion DMC 2000XB electronic personal dosimeters over a period of six days. The resulting dose rate with respect to time had a slope of t-1.024 and could be simplified to a rule of 10s: the does rate of fresh fission products from a nuclear reactor decreases by a factor of 10 for every 10 units of time.
Keywords: dose rate; nuclear reactor; fission products